ζ(0) の値

    \begin{align*} \zeta(s) &= \sum_{k=1}^\infty \frac{1}{k^s} \\ \eta(s) &= \sum_{k=1}^\infty \frac{(-1)^{k-1}}{k^s} \\ \end{align*}

とおく.

    \[\sum_{k=1}^\infty (-x)^{k-1} = \frac{1}{1 - (-x)} = \frac{1}{1 + x}\]

であることより, s = 0 のとき

    \[\eta(0) = \sum_{k=1}^\infty (-1)^{k-1} = \frac{1}{1 + 1} = \frac{1}{2}\]

また,

    \begin{align*} \eta(s) &= \zeta(s) - 2 \sum_{k=1}^\infty \frac{1}{(2k)^s} \\ &= \zeta(s) - 2 \cdot \frac{1}{2^s} \sum_{k=1}^\infty \frac{1}{k^s} \\ &= \zeta(s) - 2^{1-s} \zeta(s) \\ &= (1 - 2^{1-s}) \zeta(s) \end{align*}

であることより, s = 0 のとき

    \[\eta(0) = (1 - 2^{1-0}) \zeta(0) = - \zeta(0)\]

以上より,

    \[\zeta(0) = \boxed{- \frac{1}{2}}\]